Large-scale effects of turbidity on coral bleaching in the Hawaiian islands - Carlson, Rachel R.; Li, Jiwei; Crowder, Larry B.; Asner, Gregory P. (Frontiers in Marine Science, 2022)
Turbidity from land-based runoff has been identified as a possible driver of coral bleaching refugia, as particulate matter in turbid habitats may block excessive irradiance and alter the food supply to corals during ocean heatwaves. However, negative effects of turbidity have also been documented worldwide, and high-resolution data across reef regions are required to identify habitats where turbidity is harmful or helpful during heatwaves. We monitored turbidity across five Main Hawaiian Islands during a 2019 ocean heatwave using Planet Dove satellites (3.7 m spatial resolution, extracted at 100 m resolution) to examine relationships between turbidity and coral bleaching occurrence and severity. We also attributed turbidity to urban and non-urban land uses to determine how turbidity associated with different human activities affects coral bleaching. We found that, while turbidity had a negative relationship with coral bleaching severity, this effect weakened at higher temperatures, especially in rural areas. However, turbidity maintained a slightly negative effect on bleaching severity in urban settings. In addition, while thermal stress was the predominant driver of bleaching occurrence, interactions between temperature and local variables like turbidity and wave energy were the most significant drivers of bleaching severity. This study represents one of the first high-resolution analyses of turbid refugia at large spatial scales. We show how new data sources from remote sensing can provide scalable yet context-specific information to coastal managers addressing land-sea runoff.